1262. Salvage Therapies for Carbapenem Resistant Acinetobacter baumanii Outbreak in a Tertiary Care Center. (4th December 2021) - Lai, Lauren; Rose, Lucia; king, Madeline; Fraimow, Henry; Byrne, Dana D
Abstract: Background: The 2019 Antimicrobial Resistance Threat Report cites carbapenem-resistant Acinetobacter baumanii (CRAB) as an urgent threat causing > 700 deaths per year. 1 Acinetobacter is unique in its ability to acquire resistance determinants and pan-resistant strains have been previously reported. 2 It has the propensity to cause outbreaks, especially in critically ill populations due to its ability to survive on surfaces. 3, 4 In 2018, our hospital experienced a large CRAB outbreak. All strains were multi-drug resistant and most were identified by the Centers for Disease Control as containing OXA-23 ß-lactamase. Standard of care (SOC) was limited to agents with high toxicity potential, and thus we explored emerging therapies. In collaboration with Shionogi Inc., we obtained compassionate use cefiderocol as salvage therapy in patients failing SOC. We present our experience utilizing various treatments for CRAB infections during a hospital outbreak. Methods: We performed a retrospective chart review in adult patients with a CRAB infection treated with either cefiderocol or SOC for greater than 2 days from 08/2017 - 01/2020. SOC included use > 1 of the following: tigecycline, meropenem, polymyxins, amikacin, or eravacycline. At the time of our outbreak, we developed an institutional algorithm delineating which therapy to initiate depending on infection type. Demographic characteristics, illness severity scores, type of infection, and patient outcomes were evaluated. Results: The median age [IQR] for the cefiderocol group was 57.5 [42 to 69] versus 60 [50 to 65] in the SOC group. Illness severity scores were lower in the cefiderocol group: SOFA median value [IQR] 3.5 [1.5 - 5] versus 5 [2 - 7] and CCI median value [IQR] was 3 [2.00 -3.00] versus 3 [2 -5] (Table 1). In hospital mortality was similar in both groups with the cefiderocol group having 50% in hospital mortality versus 42.2% in the SOC group. 28-day mortality was 62.6% in the cefiderocol group versus 42.4% in the SOC group (Table 2). Conclusion: Cefiderocol may be a viable option for salvage therapy for CRAB infection. Our cohort illustrated similar outcomes as standard therapy. This study is limited by a small sample size receiving cefiderocol and the significant delay associated with obtaining cefiderocol at the time. Disclosures: Lucia Rose, PharmD, Allergan (Speaker's Bureau)Paratek (Employee) Madeline king, PharmD, Tetraphase (Speaker's Bureau) Henry Fraimow, MD, Astellas pharma (Grant/Research Support)Merck (Grant/Research Support)Shionogi (Consultant, Grant/Research Support, Scientific Research Study Investigator) Dana D. Byrne, MD, MSc, Merck (Employee)